Canine Mammary Carcinoma With Vacuolated Cytoplasm: Glycogen-Rich Carcinoma, a Histological Type Distinct From Lipid-Rich Carcinoma. Issue 1 (January 2021) - Muscatello, Luisa Vera; Papa, Valentina; Millanta, Francesca; Sarli, Giuseppe; Bacci, Barbara; Cenacchi, Giovanna; Poli, Alessandro; Giudice, Chiara; Brunetti, Barbara
Lipid-rich carcinoma is a rare histotype of canine mammary tumors with cytoplasmic vacuolation. In humans, glycogen-rich carcinoma, secretory carcinoma, and myoepithelial neoplasms are included in the differential diagnosis for lipid-rich carcinoma. The aim of the study was to investigate the existence of histotypes other than lipid-rich in canine mammary carcinomas with vacuolated cytoplasm using a diagnostic algorithm based on histopathology, histochemistry, immunohistochemistry, and ultrastructure and to evaluate the molecular phenotype of these neoplasms. Ten mammary carcinomas were collected, histologically reviewed, and subjected to histochemistry (PAS, PAS with diastase, Alcian blue, Sudan III [1 case], and Congo red [1 case]); immunohistochemistry for CK19, CK5/6, CK14, p63, calponin, vimentin, ER, PR, and HER2; and transmission electron microscopy (TEM). Cytokeratin immunolabeling demonstrated the epithelial origin of all tumors. Sudan III and TEM confirmed the diagnosis of lipid-rich carcinoma in 8 tumors (one amyloid-producing). One tumor was reclassified as a glycogen-rich carcinoma based on PAS reactivity that was diastase-labile, and a second tumor was reclassified as a carcinoma-and-malignant myoepithelioma based on the differentiation markers. Lipid-rich carcinomas were basal-like (5/8), null-type (2/8), and luminal A phenotype (1/8). The glycogen-rich carcinoma was basal-like, while the carcinoma-and-malignant myoepithelioma was luminal A. Vacuolated morphology of neoplastic cells in canine mammary carcinoma can indicate either a neoplasm of luminal epithelial origin with cytoplasmic lipid or glycogen, or vacuolated neoplastic suprabasal myoepithelial cells. Glycogen-rich carcinoma is a novel histological type that should be considered in the differential diagnosis for canine mammary carcinomas with vacuolated cytoplasm.